ANALISIS NILAI TAMBAH DAN PENDAPATAN USAHA INDUSTRI ”KEMPLANG” RUMAH TANGGA BERBAHAN BAKU UTAMA SAGU DAN IKAN - Idham Alamsyah (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The objectives of this research are 1) to calculate the income of home industri kemplang”Berkat”, and 2) to calculate the cost price, the break even point, and the value added of raw materials of kemplangs produced The analyses show that the “Berkat” received Rp 979.535,88 per month income. The cost price of each sardines and kakap kemplangs are Rp 8.116,58 per kg and Rp 10.380,85 per kg. There will be break even point when the selling amount of sardines and kakap kemplangs each are 573,70 kgs or Rp 4.876.479,88 and 42,50 kgs or Rp 637.448,35 per month. The additional value gained by tapioca and sardines from the processing of sardines kemplang is Rp 583,60 per kg. While the additional value gained by tapioca and kakap from the processing of kakap kemplangs is Rp 6.795,83 per kg.